Photoimmunotherapy of residual disease after incomplete surgical resection in head and neck cancer models. (11th May 2016) - Moore, Lindsay S.; de Boer, Esther; Warram, Jason M.; Tucker, Matthew D.; Carroll, William R.; Korb, Melissa L.; Brandwein‐Gensler, Margaret S.; van Dam, Gooitzen M.; Rosenthal, Eben L.
Abstract: Antibody‐based photodynamic therapy, or photoimmunotherapy (PIT), is a novel, targeted cancer therapy, which can serve as both a diagnostic and a therapeutic agent. The primary objective of this study was to evaluate the capacity of panitumumab‐IRDye700DX (Pan‐IR700) to eliminate microscopic tumor remnants in the postsurgical setting, which was accomplished using novel in vitro and in vivo models of residual disease after incomplete resection. Additionally, PIT was evaluated in fresh human‐derived cancer tissue. To determine a threshold for cellular regrowth after PIT, an in vitro assay was performed using a range of cells representing microscopic disease quantities. Long‐term growth inhibition was induced after treatment of 5 × 10 3 and 1 × 10 4 cells at 6 J. A novel in vivo mouse model of subtotal tumor resection was used to assess the effectiveness of Pan‐IR700 mediated PIT to eliminate residual disease and inhibit recurrence in the post‐surgical wound bed. Mice receiving surgical treatment plus adjuvant PIT showed a threefold and fourfold reduction in tumor regrowth at 30 days post PIT in the 50% and 90% subtotal resection groups, respectively (as measured by bioluminescence imaging), demonstrating a significant ( P  < 0.001) reduction in tumor regrowth. To determine the translatability of epidermal growth factor receptor (EGFR)‐targeted PIT, SCCHN human tissues ( n  = 12) were treated with Pan‐IR700. A significant reduction ( P  < 0.001) in ATP levels was observed after treatment with Pan‐IR700 and 100 J cm −2 (48% ± 5%) and 150 J cm −2 (49% ± 7%) when compared to baseline. Targeting EGFR with Pan‐IR700 has robust potential to provide a tumor‐specific mechanism for eliminating residual disease in the surgical setting, thereby increasing therapeutic efficacy, prolonging progression‐free survival, and decreasing morbidity. Abstract : Photoimmunotherapy (PIT) is a novel, cancer‐targeted technology with the potential to induce phototoxic damage to tumor cells while sparing precious adjacent normal tissue. Given the ability of PIT agents to be used as dual diagnostic and therapeutic agents, many experts believe that this modality would be best used to eradicate residual microscopic disease after incomplete surgical resection; however, most existing studies in this field use whole‐tumor animal models. In order to assess the therapeutic potential of PIT in the proposed role of an adjuvant post‐surgical treatment modality, we designed novel in vitro and in vivo models of microscopic and residual disease, as well as obtained fresh human tissue to assess the clinical translatability of this technology.